Gazimağusa İlçesinde İkamet Eden Yetişkin Obez Kadınlarda Besin Çeşitliliğinin ve Yaşam Kalitesinin Değerlendirilmesi - Tay, Özlem (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
This study was planned with the aim of assesing nutrition diversity and life quality of corpulent women and conducted with 130 corpulent women in between 18-65 age range at famagusta district of Turkish Republic of Northern Cyprus (TRNC). A questionnaire was used to collect information about the demographic characteristics and eating habits of the women participating in the study. In order to determine nutritional status, retrospective 24-hour food consumption record and also nutritional diversity index of FAO (Food and Agriculture Organization) was used. To determine the life quality perceptions of corpulent individuals, The Obese Individuals Specific Quality of Life Scale was utilized. %43.1 of the women participating in the study are in the 18-45 age group and %56,9 are in the 46-65 age group. %57.7 of the participants reported to have chronical diseases. Individuals ascertained weight average was 92.45±70.39 kg, height average 151.64±27.89 cm, Body Mass Index (BMI) average 35.31±5.19 kg/m2 , waist circumference average 109.38±11.52 cm and waist-to-hip ratio 0.91±0.11 cm. When the correlation between anthropometric measurements and life quality is analyzed, a strong and positive correlation was found between life quality and weight (kg), BMI, waist circumference (cm), hip circumference (cm), body muscle mass (kg) and body fat mass (kg) (p<0.05). According to total nutrition diversity scores of individuals; %12.3 of the participants have 0-3 points (low nutrition diversity ) and %87.7 have 6-9 points (high nutrition diversity). There was no statistically signifcant difference, in terms of obesity level and nutrition diversity scores (p>0.05). Statistically significant difference was found between the life quality scores of individuals suffering morbid obesity (=2.89) and first degree (=2.34), second degree obesity levels (=2.84) (p<0.05).

ÖZ: Bu çalıĢma obez kadınların besin çeĢitliliğini ve yaĢam kalitesini değerlendirmek amacıyla planlanmıĢ olup KKTC‟nin Gazimağusa bölgesinde yaĢları 18-65 arasında değiĢen 130 obez kadın ile yürütülmüĢtür. ÇalıĢmaya alınan kadınların demografik özellikleri ve beslenme alıĢkanlıkları hakkındaki bilgilerinin toplanabilmesi için anket formu kullanılmıĢtır. Beslenme durumlarının saptanması için geriye dönük 24 saatlik besin tüketim kaydı ayrıca FAO‟nun (Gıda ve Tarım Örgütü) besin çeĢitliliği indeksi kullanılmıĢtır. Obez bireylerde yaĢam kalitesinin değerlendirmek için „obezlere özgü yaĢam kalitesi ölçeği (OÖYKÖ) kullanmıĢtır. AraĢtırmaya katılan kadınların %43.1‟i 18-45 yaĢ, %56.9‟u 46-65 yaĢ grubundadır. Bireylerin %57.7‟si kronik hastalığı olduğunu bildirmiĢtir. Bireylerin vücut ağırlığı ortalama 92.45±70.39 kg, boy uzunluğu ortalama 151.64±27.89 cm, BKĠ ortalama 35.31±5,19 kg/m2, bel çevresi ortalama 109.38±11.52 cm, bel/kalça oranı 0.91±0.11 olarak saptanmıĢtır. Antropometrik ölçümler ile yaĢam kalitesi arasındaki korelasyonlar incelendiğinde, vücut ağırlığı, BKI, bel çevresi, kalça çevresi, vücut kas kütlesi ve vücut yağ kütlesiile yaĢam kalitesi arasında pozitif yönde güçlü iliĢki gözlemlenmiĢtir (p<0.05). Bireylerin toplam besin çeĢitliliği skorlarına göre katılımcıların; %12.3‟ü 0-3 puan arasında (düĢük besin çeĢitliliği) ve %87.7‟si 6-9 puan arasında (yüksek besin çeĢitliliği) puanına sahiptir. Obezite derecesine göre besin çeĢitliliği skorunda anlamlı bir farklılık görülmemiĢtir (p>0.05). Morbid obezlerin yaĢam kalitesi puanı ile (=2.89) 1.derece obez (=2.34) ve 2.derece obez (=2.84) olanlar arasında istatiksel olarak anlamlı fark bulunmuĢtur (p<0.05).
Beslenme ve Diyetetik Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Sağlık Bilimleri Fakültesi, Beslenme ve Diyetetik Bölümü, 2017. Tez Danışmanı: Yard. Doç. Dr. Seray Kabaran.
Keywords: Beslenme ve Diyetetik; Obezite; Obezlere Özgü Yaşam Kalitesi Ölçeği (OÖYKÖ); Besin Çeşitliliği; BKİ; Obezite; Yaşam Kalitesi; Obese Individuals Specific Quality of Life Scale; Nutrition Diversity; BMI; Obesity; Life Quality